Spectroscopic detection of aspartame in soft drinks by surface-enhanced Raman spectroscopy - Buyukgoz, Guluzar Gorkem; Bozkurt, Akif Goktug; Akgul, Nese Basaran; Tamer, Ugur; Boyaci, Ismail Hakki (SPRINGER, 2015)
Aspartame (N-L-alpha-aspartyl-L-phenylalanine methyl ester) is a low-calorie sweetener commonly used in carbonated soft drinks and beverages. In this study, a rapid and simple method was developed for the quantification of aspartame in soft drinks using surface-enhanced Raman spectroscopy (SERS) with silver nanoparticles (AgNPs). For this purpose, AgNPs were synthesized by a wet chemistry method and characterized by UV-visible spectrophotometry and transmission electron microscopy. Then, mineral water samples were spiked with different concentrations of aspartame (0-1.0 mg ml(-1)) and Raman measurements were taken on the enhancement of the aspartame Raman signal in the presence of AgNPs. The calibration curve was plotted in terms of Raman band intensity at 1,002 cm(-1) against the aspartame concentration. A good linear relationship was obtained by SERS with high determination coefficient values (R-2) for water, mineral water, and fruit-flavored mineral water, i.e., 0.969, 0.977, and 0.977, respectively. The method was validated for linearity, sensitivity, precision (intra- and inter-day repeatability), and recovery. The limit of detection and limit of quantification values of the aspartame-spiked mineral water samples were 0.17 and 0.56 mg ml(-1), respectively. Intra-and inter-day precision were 1.3 and 0.9 %, respectively. The recovery of the method was 81-95 % in the concentration range 0-0.6 mg ml(-1), and the average RSD was 7.3 %. A short analysis time (15 s), small sample requirement, and aspartame analysis without pretreatment were found with the SERS system, which may be a more practical and applicable method for specific target analysis.
Keywords: Aspartame; Surface-enhanced Raman spectroscopy; Mineral water; Silver nanoparticles; SCATTERING SERS; ACESULFAME-K; CAPILLARY-ELECTROPHORESIS; ION CHROMATOGRAPHY; SILVER COLLOIDS; SWEETENERS; FOOD; SACCHARIN; PRODUCTS; NANOPARTICLES; Food Science & Technology